Genetic diversity and selection signatures in sheep breeds - Rodrigues, Julia Lisboa [UNESP]; Braga, Larissa Graciano [UNESP]; Watanabe, Rafael Nakamura [UNESP]; Schenkel, Flávio Schramm; Berry, Donagh Pearse; Buzanskas, Marcos Eli [UNESP]; Munari, Danísio Prado [UNESP] (Springer Nature, 2025)
Natural and artificial selection in domesticated animals can cause specific changes in genomic regions known as selection signatures. Our study used the integrated haplotype score (iHS) and Tajima’s D tests within non-overlapping windows of 100 kb to identify selection signatures, in addition to genetic diversity and linkage disequilibrium estimates in 9498 sheep from breeds in Ireland (Belclare, Charollais, Suffolk, Texel, and Vendeen). The mean observed and expected heterozygosity for all the sheep breeds were 0.353 and 0.355, respectively. Suffolk had the least genetic variation and, along with Texel, had slower linkage disequilibrium decay. iHS and Tajima’s D detected selection signatures for all breeds, with some regions overlapping, thus forming longer segments of selection signatures. Common selection signatures were identified across iHS and Tajima’s D methods for all breeds, with Belclare and Texel having several common regions under positive selection. Several genes were detected within the selection signature regions, including ITGA4, TLR3, and TGFB2 related to the immune system against endoparasites; DLG1, ROBO2, MXI1, MTMR2, CEP57, and FAM78B related to reproductive traits; WDR70 related to milk traits; SCHM1 and MYH15 related to meat traits; and TAS2R4, TAS2R39, and TAS2R40 related to adaptive traits. In conclusion, our results demonstrated moderate genetic diversity in the sheep breeds and detected and characterized selection signatures harboring genes associated with reproductive traits, milk production, meat production, and adaptive traits such as endoparasite resistance.
Keywords: Genomics; Linkage disequilibrium; Ovis aries; Selective sweep; Single-nucleotide polymorphism; Site frequency spectrum